Considering the question of the formation of equivalent exchange in the economic relations of enter-prises dairy subcomplex - Tarasiuk, N. M.; Adler, O. O.; Ratushniak, O. H. (Visnyk of Vinnytsia Politechnical Institute, 2013)
The equivalence of exchange in the economic relations of enterprises is analyzed, the optimal price level for milk and milk products at different stages of the production process is calculated and the profit distribution between different areas of dairy production agriculture is conducted in the paper.